2017
DOI: 10.1039/c6ra26279a
|View full text |Cite
|
Sign up to set email alerts
|

Electrically conductive hydrogel-based micro-topographies for the development of organized cardiac tissues

Abstract: In this study, we developed conductive microgrooved tissue constructs, leading to the formation of highly packed and uniaxially oriented cardiac cytoarchitecture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(46 citation statements)
references
References 64 publications
1
45
0
Order By: Relevance
“…ECHs deliver biomimetic topographical and electrical cues in vitro to form highly oriented cellular constructs with tissue-level functionality (d). [181] conductive materials from inherently non-conductive polymers, through the conjugation of a choline-based Bio-IL [20]. Our results demonstrated that GelMA/Bio-IL ECHs could be used to modulate the proliferation and contractile function of primary rat CMs in vitro.…”
Section: Tissue Engineeringmentioning
confidence: 74%
See 3 more Smart Citations
“…ECHs deliver biomimetic topographical and electrical cues in vitro to form highly oriented cellular constructs with tissue-level functionality (d). [181] conductive materials from inherently non-conductive polymers, through the conjugation of a choline-based Bio-IL [20]. Our results demonstrated that GelMA/Bio-IL ECHs could be used to modulate the proliferation and contractile function of primary rat CMs in vitro.…”
Section: Tissue Engineeringmentioning
confidence: 74%
“…In another study by Navaei et al, 50 m microgrooves were incorporated into gelatin GelMA hydrogels with electrically conductive GNRs (Fig. 9d) [181]. Fluorescent images revealed uniform, dense, and highly aligned cellular organization, as well as enhanced cytoskeletal alignment and cellular connectivity.…”
Section: Tissue Engineeringmentioning
confidence: 79%
See 2 more Smart Citations
“…Nanomaterials such as carbon nanotubes (CNTs) (Martinelli et al, 2012;Patel et al, 2016), gold (Au) nanorods (Fleischer et al, 2014;Navaei et al, 2016Navaei et al, , 2017Shin et al, 2016), graphene oxide (GO) nanoflakes (Shevach et al, 2013;Park et al, 2015a), silicon nanowires (Park et al, 2015b;Tan et al, 2017), and iron oxide (Han et al, 2015;Richards et al, 2016) in conjugation with the extracellular and intercellular microenvironments of transplanted cells are believed to enable regeneration of injured CMs Amezcua et al, 2016;Mehrali et al, 2017). Regenerative properties of CMs can be measured by obtaining electrical conductivity, protein adsorption affinity, intracellular signaling pathways, and magnetic properties.…”
Section: Cardiac Tementioning
confidence: 99%